Exposure of Platelets to Dengue Virus and Envelope Protein Domain III Induces Nlrp3 Inflammasome-Dependent Platelet Cell Death and Thrombocytopenia in Mice - Lien, Te-Sheng; Chan, Hao; Sun, Der-Shan; Wu, Jhen-Cheng; Lin, You-Yen; Lin, Guan-Ling; Chang, Hsin-Hou (Frontiers in Immunology, 2021)
In tropical and subtropical regions, mosquito-borne dengue virus (DENV) infections can lead to severe dengue, also known as dengue hemorrhage fever, which causes bleeding, thrombocytopenia, and blood plasma leakage and increases mortality. Although DENV-induced platelet cell death was linked to disease severity, the role of responsible viral factors and the elicitation mechanism of abnormal platelet activation and cell death remain unclear. DENV and virion-associated envelope protein domain III (EIII), a cellular binding moiety of the virus particle, highly increase during the viremia stage. Our previous report suggested that exposure to such viremia EIII levels can lead to the death of megakaryocytes. Here we found that both DENV and EIII could induce abnormal platelet activation and predominantly necrotic cell death pyroptosis. Blockages of EIII-induced platelet signaling using the competitive inhibitor chondroitin sulfate B or selective Nlrp3 inflammasome inhibitors OLT1177 and Z-WHED-FMK markedly ameliorated DENV- and EIII-induced thrombocytopenia, platelet activation, and cell death. These results suggest that Nlrp3 inflammasome is a feasible target for developing therapeutic approaches against dengue-induced platelet defects.